FENOFIBRATE IN THE COMPLEX TREATMENT OF COMPLICATIONS OF TYPE 2 DIABETIC RETINOPATHY - Parpibaeva Dinara Ayupovna; Salayeva Muborak Saidabdullayevna; Salimova Nargiza Djurabaevna; Ergashov Nodirbek Shermuxamat o’g’li; Buvamuxamedova Nasiba Taxirovna (Journals Park Publishing, 2023)
Today, diabetes mellitus is considered a “pandemic”, and the number of patients with this disease and its complications is increasing day by day. Diabetes mellitus is a severe complication of diabetic retinopathy that leads to blindness and disability in people. Timely detection, prevention and effective treatment of this complication are among the urgent tasks facing endocrinologists. Today, taking into account such risk factors as hyperglycemia, dyslipidemia and uncontrolled arterial hypertension, which play a leading role in the pathogenesis of complications of diabetic retinopathy, many studies are being carried out in the world on the effective complex treatment of this complication. This article talks about the next study conducted at the multidisciplinary clinic of the Tashkent Medical Academy.
Keywords: - Diabetes mellitus, Diabetic retinopathy, Dyslipidemia, Fenofibrate (Tricor).